Influencia de los comportamientos relacionales del venedor individual sobre la satisfaction confianza y lealtad del comprador en un contexto de PYMES industriales - Pedro Juan Martín Castejón; Sergio Román Nicolás; Estela Fernández Sabiote (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2011)
The present study is built on the principles of relationship selling in a context of industrial Small and Medium-sized Enterprises (SMEs). The research specifically analyses the influence of customer-oriented selling and ethical sales behaviors on customer satisfaction, trust and loyalty to the seller company. Results, based on a sample of 219 SMEs, revealed that both customeroriented selling and ethical selling behaviors positively and directly influence satisfaction and trust, and indirectly influence loyalty. In addition, ethical selling positively influences customer-oriented selling. Overall, this study highlights the key role of the salesforce in industrial settings and are likely to stimulate further attention both from theory and management on the study of the salesforce efficient management.
Keywords: M31; 330; customer-oriented selling; ethical selling; relational variables; industrial smes